Internet Use, Life Satisfaction, and Subjective Well-Being Among the Elderly: Evidence From 2017 China General Social Survey - Yang, Hua-lei; Wu, Yuan-yang; Lin, Xue-yu; Xie, Lin; Zhang, Shuo; Zhang, Si-qing; Ti, Shi-ming; Zheng, Xiao-dong (Frontiers in Public Health, 2021)
Purpose: The research objectives of this study are to test the scientific propositions of whether Internet use promotes life satisfaction among the elderly, whether there is variability in the effect of Internet use on the well-being of the elderly, and through what channels Internet use affects the elderly's life satisfaction. Method: Using data from the 2017 Chinese General Social Survey (CGSS), this paper employed linear regression, ordered logit model, and the propensity score matching (PSM) approach to investigate the association of Internet use with life satisfaction among the elderly in China. Results: The results show that Internet use was significantly and negatively associated with the life satisfaction of the Chinese elderly. Further analysis on group heterogeneity demonstrates that the negative association was more prominent among the participants who were males, at a lower age, had lower income and education, non-agricultural registered, and relatively healthy. Finally, the mediating effect indicates that Internet use may affect life satisfaction among the elderly through the channel of reducing their perceptions of social justice. Conclusions: In order to avoid the negative effects of using the Internet, the following policy suggestions are put forward: Improve the elderly's attitudes toward Internet use; pay attention to the sense of fairness of the elderly to improve life satisfaction; guide the elderly to reduce the time of using the Internet.